STRATEGI GURU DALAM MENGATASI ANAK DISLEKSIA KELAS 3 DI SDN 31 CAKRANEGARA - Asriani Saiful; Hari Witono (Program Studi PGSD, FKIP, Universitas Mataram, 2023)
Dyslexia is a learning disorder that affects a person's ability to read, spell and write. This disorder is not related to intelligence problems or visual deficiencies, but is caused by difficulties in processing and understanding letters, words and written symbols. This study aims to explore the strategies used by teachers in overcoming dyslexic children in grade 3 of SDN 31 Cakranegara. The research method used is qualitative method with descriptive type. The researcher observed and interviewed a grade 3 teacher who has experience in teaching dyslexic children. The results showed that teachers used strategies in overcoming dyslexic children in grade 3, namely learning material adjustment strategies, multisensory approaches, individualized support, and collaboration with parents.